Unshackling Grandi - Ágúst Skorri Sigurðsson 1984- (2024)
A former island called Örfirisey is now surrounded by landfills (land reclamation) forming a peninsula known as Grandi. With massive landfills since the early 20th century and up to 2007 when the coastline of Grandi mostly reached its current form, it is yet to be fully built and developed. On Örfirisey stands the area’s most defining aspect, the largest oil reserves of Iceland, built at the edge of Reykjavík’s city center. With the world moving away from fossil fuels and the current government’s aim to free Iceland from them and be carbon neutral by 2040, I want to look into the future of the area. What does this development mean for the oil reserves and for Grandi? Climate crisis is a major incentive for moving away from fossil fuels and Grandi is very exposed to the elements, as it is built to guard the old harbor. The landfill only has an average of a little over 4-meter height above sea level. With aforementioned situations in mind, I want to explore the future of Grandi and Örfirisey as it develops in context with the city center and the old harbor. Although the area is currently in disarray, it also holds great potential, that could see the area bloom in the future.